ANALISIS KELAYAKAN PENGEMBANGAN OBJEK WISATA TAMAN AGROWISATA TENAYAN RAYA KOTA PEKANBARU - Fitri, Febriani; Eriyati, Eriyati; Hendro, Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to find out if Taman Agrowisata Tenayan Raya in Pekanbaru City is well-developed. In this study used two types of data, namely primary and secondary data. The data analysis methods used in this study are quantitative desktriptive methods. This analysis aims to simplify data into a form that is easier to understand and interpret. In this research the collected data is processed by looking at the technical aspects, financial aspects, market aspects and environmental aspects. In the financial aspects used method of analysis of investment criteria by doing the calculation of Net Present Value, Net Benefit Cost Ratio, Internal Rate of Return and Payback Period. The results of this research show that Taman Agro tourism Tenayan Raya City Pekanbaru deserves to be developed. From financial analysis at 10% interest rate, got NPV in amount Rp 34.933.139. The analysis of BCR obtained a value of 1.011 indicating that for each cost Rp. 1 issued will provide benefits in the amount of 1.011. In addition IRR analysis gained a value in the amount of 10.35% which indicates that there will be Payback when the interest rate reaches 10,35%. Based on the calculation of the Investment return criteria (Payback period), Taman Agrowisata Tenayan Raya able to restore initial capital early in a period of 4 years 2 months.Keyword: Feasibility Study, Agrourism, Tenayan Raya